Engineering of software the continuing contributions of Leon J. Osterweil - Tarr, Peri L.; Wolf, Alexander L. (Springer, 2011)
Software engineering research can trace its roots to a few highly influential individuals. Among that select group is Leon J. Osterweil, who has been a major force in driving software engineering from its infancy to its modern reality. For more than three decades, Prof. Osterweil's work has fundamentally defined or significantly impacted major directions in software analysis, development tools and environments, and software process - all critical parts of software engineering as it is practiced today. His exceptional contributions to the field have been recognized with numerous awards and honors through his career, including the ACM SIGSOFT Outstanding Research Award, in recognition of his extensive and sustained research impact, and the ACM SIGSOFT Influential Educator Award, in recognition of his career-long achievements as an educator and mentor. In honor of Prof. Osterweil's profound accomplishments, this book was prepared for a special honorary event held during the 2011 International Conference on Software Engineering (ICSE). It contains some of his most important published works to date, together with several new articles written by leading authorities in the field, exploring the broad impact of his work in the past and how it will further impact software engineering research in the future. These papers, part of the core software engineering legacy and now available in one commented volume for the first time, are grouped into three sections: flow analysis for software dependability, the software lifecycle, and software process.